High Susceptibility of Histidine to Charge Solvation Revealed by Cold Ion Spectroscopy. Issue 49 (8th November 2017) - Pereverzev, Aleksandr Y.; Kopysov, Vladimir; Boyarkin, Oleg V.
Abstract: Histidine remained the last aromatic amino acid for which the intrinsic spectroscopic properties and structures were obscure. We measured the UV and IR spectra of protonated histidine, isolated in the gas phase, using photofragmentation cold ion spectroscopy. Unexpectedly, the UV absorption appears strongly redshifted relative to that of the cation in aqueous solutions. In investigating this phenomenon, we solved the geometries of all abundant conformers using IR conformer‐selective spectroscopy and ab initio quantum chemical calculations. In all of the structures, the proton resides on the imidazole ring. The measured UV spectra of protonated methylimidazole, histamine and histidine, together with calculations of the electronic spectra for the latter, suggest that, in comparison with other aromatic amino acids, such location of proton makes UV absorption of histidine highly sensitive to the local environment of its side chain. Abstract : Upon desolvation, protonated histidine exhibits an unexpected redshift of its UV absorption. Cold ion spectroscopy and theoretical calculations have been used to solve 3D structures of HisH + in the gas phase and to reveal the origin of the UV redshift. The location of the proton on the aromatic ring of His makes its UV absorption highly susceptible to non‐covalent interactions in biomolecules.